2015
DOI: 10.1155/2015/482146
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of MicroRNA-182 in Cancers: A Meta-Analysis

Abstract: Objective. MicroRNA-182 (miR-182) exhibits altered expression in various cancers. The aim of this study was to investigate the predictive value of miR-182 expression for cancer patient survival. Methods. Eligible studies were identified through multiple search strategies, and the hazard ratios (HRs) for patient outcomes were extracted and estimated. A meta-analysis was performed to evaluate the prognostic value of miR-182. Results. In total, 14 studies were included. A high miR-182 expression level predicted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…MiR-182-5p belongs to the miR-183 family and miR-182-5p is encoded on chromosome 7q31-34 [18]. Medimegh et al (2014) examined expression of miR-182 in the following three groups: TNBC, NTNBC (Non Triple Negative Breast Cancer; Luminal A, Luminal B and HER2 positive patients) and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-182-5p belongs to the miR-183 family and miR-182-5p is encoded on chromosome 7q31-34 [18]. Medimegh et al (2014) examined expression of miR-182 in the following three groups: TNBC, NTNBC (Non Triple Negative Breast Cancer; Luminal A, Luminal B and HER2 positive patients) and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of miR-182 is increased in breast tumors compared with normal breast tissue (39) and in serum of patients with breast cancer (40). High miR-182 is associated with worse outcome in a meta-analysis of 10 studies (41). Overexpression of miR-182 increases the sensitivity of breast cancer cell lines to poly(ADP-ribose) polymerase 1 (PARP1) inhibitors (28, 42), similar to that observed in BRCA1-deficient cells and tumors (42).…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal analysis of circulating miRNAs revealed rno‐miR‐182 as a potential predictive biomarker, which is 96% identical in sequence to its human homolog. miR‐182 is another oncomiR that is commonly upregulated in multiple cancers and predicts poor survival in patients . Chen et al observed that high levels of serum miR‐182 in patients with HCC were significantly associated with decreased survival after surgery.…”
Section: Discussionmentioning
confidence: 99%